Philological Analysis of the Sundanese Folklore 'Lutung Kasarung’ - Subandiyah, Heny; Supratno, Haris; Permata, Resdianto; Fahri, Fahri; Abida, Fithriyah Inda Nur (Universitas Pendidikan Mandalika, 2023)
One of the most well-known and beloved Sundanese folklore stories is the